Boiler tube remaining life according to Larson-Miller parameter - Mohamad Akram, Mohd Khairil Ridzwan (2023)
This research aims to address the problem of the remaining boiler tube life according to the Larson-Miller parameter (LMP). Boiler tubes are used in a wide variety of industrial applications and are subject of deterioration due to corrosion and other environmental damage. It is estimated that 10% of all power plant breakdowns are caused by creep fractures of boiler tubes. Additionally, 30% of all tube failures in boilers and reformers are a result of creep. This deterioration can cause significant damage to the boiler and its associated equipment, leading to decreased efficiency and increased downtime. Therefore, the evaluation of boiler tube remaining life is essential in order to ensure the continued reliability and performance of the boiler system. The LMP is a widely accepted tool for evaluating the remaining life of boiler tubes which is based on a combination of temperature, stress and time. The LMP is used to calculate the remaining life of boiler tubes and is based on the assumption that the boiler tube will fail when the LMP reaches a certain critical value This research aims to analyse the LMP, its limitations and its ability to accurately predict the remaining life of boiler tubes. From the study it shows that LMP is a theoretical method for estimating boiler tube life based on pressure and temperature, but it does not take into account the boiler's condition or atmosphere. The research also reveals that the highest temperature was associated with the lowest stress level i.e., materials with higher LMP values are more susceptible to severe creep damage and as temperature increased in the boiler, the remaining life of the tube decreased significantly ( the remaining life of a tube SA 213 was less than 300 hours at 1139 K).